Caring for home‐dwelling parents with dementia: A qualitative study of adult‐child caregivers' motivation. Issue 6 (7th August 2020) - Dombestein, Heidi; Norheim, Anne; Aase, Karina
Abstract: Aim: To explore adult children's motivation in caregiving for their home‐dwelling parents with dementia. Design: Qualitative design with a phenomenological approach. Methods: Semi‐structured individual interviews with 21 adult sons and daughters who were caregivers for a parent with dementia. Data were analysed using systematic text condensation. Results: Inspired by self‐determination theory, three categories were identified in the empirical data representing the main motivational drivers for adult‐child caregivers: relatedness (to the parent with dementia, the parent's spouse, other persons), competence (in handling dementia, in the parent's need) and autonomy (freedom of choice, innate values and tasks). Caregivers report relatedness as their key motivational driver. These results imply that nurses and other health professionals should value the importance of relatedness when interacting with dementia caregivers and establish belonging support structures. Further research should generate more knowledge of the positive motivational drivers, including interventions to improve relatedness, competence and autonomy.